Rain-Induced Disaster Alarm System Using Microwave and Acoustic Sensing - Zamora, J.L.F (Archīum Ateneo, 2011)
This paper focuses on the design and development of a rain-induced disaster alarm system based on three years' worth of wireless and acoustic measurements of actual rain events. A hybrid wireless network involving a 26 GHz microwave backhaul link, the transceivers of which are 4 km apart, composes the integrated rain measurement via the received signal level (RSL). Point sensors in the form of acoustic recorders are strategically deployed along the 4-km link on one data set and on a 3×3 grid 100 m apart on another data set, measuring the signal power of the rain as it approaches the ground. The collective analysis of the parameters under monitoring leads to the establishment of appropriate rain-related disaster warning.